Measuring trade in financial services - ARNDT, H.W. (PSL Quarterly Review, 2013)
Although it has always been present, the importance of trade in financial services has increased greatly in the past two decades with the internationalisation of banking and the growth of international financial centres as the bases for offshore currency markets and other activities linking national capital markets. The question naturally arises how to measure the value and growth of this trade in financial services. The issues involved in this question are closely related to the difficulties that have been encountered in the treatment of financial enterprises in social accounts for national economies. In this context, the author investigates. JEL: F30, G15